Subjectivities of nurses 'work in the organ donation process: sociopoetic as a method (Research, Society and Development, 2021)
The objective of this article was to reveal the subjectivities of nurses' work in the process of organ donation with the use of sociopoetics as a method. Qualitative research, developed with 8 nurses, working in a municipality in the extreme south of the state of Bahia, Brazil. The production of data considered the researcher group as a device and the stimulus of the senses, for the expression of subjectivities. The activities developed in the dynamics of the researcher group were recorded and the audios were transcribed, textualized and categorized, according to Bardin's content analysis. The study fulfilled the ethical requirements of research with human beings. The results are presented in a table, based on the following transversal themes of the subjectivities expressed by the stimulus of meaning: unpredictability of everyday life, importance of teamwork, humanization and welcoming and hope as a motivating element for work. The discussion expressed that the use of sociopoetics as a method made it possible to unveil the imaginative dimension of nursing professionals about their activities, analyzing several aspects, such as unveiling the subjectivities of nurses' work in the organ donation process, in the statements of nurses and the dimensions present in the work process of organ and tissue donation in the hospital environment, among other aspects of the emerging content of the Research Group. Thus, it was perceived the unpredictability of daily life, the importance of teamwork, humanization and welcoming and hope, as motivating elements for work and factors that influence organ donation and transplantation.